Evaluasi Implementasi Sistem Informasi Manajemen Pendidikan Melalui School Information System (SIS) Edunav di SMP Semesta - Lukman Nul Hakim; Mulyanto Mulyanto (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this research are (1) to analyze effectiveness of implementation Edunav School Information System (SIS) in Semesta Middle School; (2) to analyze the resisting factors of implementation Edunav School Information System (SIS); (3) to analyze the supporting factors of implementation Edunav School Information System (SIS); (4) to analyze the success Edunav SIS’s implementation. The research was conducted at Semesta Junior High School located to evaluate effectiveness of implementation Edunav School Information System (SIS). The population in this study were principal, administration, students, teachers, and parents and students. This paper uses evaluative research using CIPP model. The mixed approach is used in this research. Quantitative descriptive approach using a quantitative descriptive questionnaire to measure the effectiveness of Edunav’s SIS implementation. The findings indicate that (1) The result of the assessment of the contex, input, process and product with the CIPP model show that the implementation of SIS Edunav is very good for all indicators. (2) Resisting factors, namely the lack of participation of parents and socialization is not optimal. (3) The implementation of SIS Edunav has many supporting factors such as foundation support, human resources capabilities and easy of access. (4) In general, management system of school information in Semesta Middle School well.